Heaven Is Empty: A Cross-Cultural Approach to Religion and Empire in Ancient China - Marsili, Filippo (SUNY Series in Chinese Philosophy and Culture Ser, 2018)
Intro -- Contents -- Acknowledgments -- Author's Note -- Introduction: An Empire without a "Religion" -- Monotheisms and Globalizations -- The Argument: Metaphysics in Historical Narratives -- Elusive Rulers, Lacunose Accounts, Inadequate Models -- Overlapping Historical and Cultural Contexts -- Grappling with the Issue of "Religion" in Chinese History and Society -- Time and Space: The Structure of Heaven Is Empty -- 1 Readings of the "Sacred" -- The Hegemony of Monotheism, Founding Fathers, and the Necessity of a Chinese Religion -- Chinese Religions and Comparative Approaches -- An Ethnocentric Conundrum: Civilization without Religion -- The Axial Age: History Becomes Philosophy, and Philosophy Reverts to Religion -- Philology as Mythology -- Rituals for the Living and for the Dead -- Conclusions: Comparativism, Ambiguity, and Intercultural Dialogue -- 2 Writing the Empire Ex Pluribus Plurima -- Empires, Historiography, and Cultural Unification -- The Points of Views of the First History of China -- Ritual and Memory in Early Imperial China -- The Solitude of the Sages: The Elusiveness of Li and the Unification of China -- The Recovery and Re-creation of Li after Emperor Wu -- Everything Comes Together: Ban Gu and "The Treatise on the Five Phases" -- The Classicists and "the People" -- Of Omens, Emperors, and Men -- Historiography as an Educational Journey -- Conclusions: "Every Structure Is a Hidden God" -- 3 Narrating the Empire Metaphysics without God, "Religions" without Identity -- Heaven, Fortune, and Universalism in Early Chinese and Greco-Roman Historiography -- The Records, Universalism, and the Extension of Civilization -- Universalism in Polybius -- A Brief Cultural History of Heaven -- Gaozu, Empress Lü, Heaven and Yin and Yang's Anomalies -- Liu Bang, a Snake, and Heaven's Involvement in the Fall of the Qin